Criminal Liability for Asset Forfeiture in Indonesia Concerning Drug Traffickers - Jhoni Fernando Sinaga; Mahmud Mulyadi; Marlina Marlina; Darmawan Darmawan (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The concept of criminal responsibility, involving both mens rea (mental state) and actus reus (physical act), is essential in determining liability for criminal acts in Indonesia. In narcotics trafficking cases, the application of these elements plays a crucial role in establishing accountability, especially when it comes to asset forfeiture. However, there are challenges in effectively applying these principles, particularly the concept of strict liability, which remains unclear in certain legal provisions regarding asset seizure. The research aims to analyze how mens rea and actus reus are applied in narcotics-related crimes in Indonesia and their implications for asset confiscation. Using case studies and legal analysis, the research identifies gaps in the application of strict liability and highlights inconsistencies in the law. The results show that although the principle of strict liability is implicitly applied in the Narcotics Law, there is a lack of clarity in its implementation, which leads to inconsistencies in the legal process. This research highlights the need for clearer legal frameworks and more consistent application of strict liability to enhance the effectiveness of narcotics crime deterrence. The implications of this research suggest that legal reforms are necessary to improve asset seizure processes and overall law enforcement effectiveness in Indonesia, providing a foundation for future research on the integration of criminal and civil aspects in narcotics cases.